x+x=8
+ +
y-y=6
= =
13 8
Answers
Answered by
1
Answer:
x/x-1 + x-1/x =13/6
x2+(x-1)2/x(x-1)=13/6
x2+x2+1-2x/x2-x=13/6
2x2-2x+1/x2-x=13/6
6(2x2-2x+1)=13x2-13x
12x2-12x+6=13x2-13x
13x2-12x2-13x+12x-6=0
x2-x-6=0
x2-3x+2x-6=0
x(x-3)+x(x-3)=0
(x-3)(x+2)=0
x-3=0 n x+2=0
x=3 n x=2
Answered by
0
Answer:
Hope it helps you.......
Attachments:
![](https://hi-static.z-dn.net/files/dde/f60de506c338ee63c1624c23517cfaf2.jpg)
Similar questions
Math,
6 months ago
Social Sciences,
6 months ago
Computer Science,
6 months ago
Math,
1 year ago
English,
1 year ago